A study on sanitary and hygiene practices in Chungwang VDC of Dhankuta District, Eastern Nepal - Rayamajhi, RB; Budhathoki, SS; Ghimire, A; Niraula, SR; Khanal, VK; Neupane, B; Shakya, B; Pokharel, PK (Journal of Chitwan Medical College, 2014)
Lack of proper practices of sanitary habit leads to ill health of household members, community and the nation as a whole. Provision of sanitary latrines and safe drinking water are necessary to prevent fecal oral transmission of infections. To conduct a study on sanitary hygiene and practices among the residents of Chungwang VDC. 97.4% of the respondents wash their hands with soap or other detergents though 99.3% of them had soaps at their home on observation. Similarly, 81.2% of them had toilet at home but only 79.2% used on regular basis. Basic hand washing was practiced by everyone during/after defecation and before meal but the importance of it after cleaning the bottom and nose of children and before preparing the meal was known to few of the participants. A need of behavioral change regarding optimum hygiene practices is required among the participants. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10856 Journal of Chitwan Medical College 2014; 4(2): 20-24